2008
DOI: 10.1640/0002-8444(2008)98[117:amadsf]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular Mycorrhizas and Dark Septate Fungi in Lycopodium paniculatum (Lycopodiaceae) and Equisetum bogotense (Equisetaceae) in a Valdivian Temperate Forest of Patagonia, Argentina

Abstract: Arbuscular Mycorrhizas and Dark Septate Fungi in Lycopodium paniculatum (Lycopodiaceae) and Equisetum bogotense (Equisetaceae) in a Valdivian Temperate Forest of Patagonia, Argentina

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 36 publications
2
13
0
8
Order By: Relevance
“…However, in order to clarify conflicting evidence for symbionts we made our own critical observations. As reported by previous authors (Boullard, ; Dhillon, ; Fernández et al, ), we found both AM fungi with vesicles and dark septate hyphae in old roots of six species of Equisetum from different habitats, viz., E. arvense, E. fluviatile, E. giganteum, E. hyemale, E. telmateia and E. variegatum . Fungi were never observed in young roots with intact apices and DNA sequencing produced negative results (Rimington et al, unpublished data).…”
Section: Systematic Surveysupporting
confidence: 89%
See 1 more Smart Citation
“…However, in order to clarify conflicting evidence for symbionts we made our own critical observations. As reported by previous authors (Boullard, ; Dhillon, ; Fernández et al, ), we found both AM fungi with vesicles and dark septate hyphae in old roots of six species of Equisetum from different habitats, viz., E. arvense, E. fluviatile, E. giganteum, E. hyemale, E. telmateia and E. variegatum . Fungi were never observed in young roots with intact apices and DNA sequencing produced negative results (Rimington et al, unpublished data).…”
Section: Systematic Surveysupporting
confidence: 89%
“…Whether or not dark septate hyphae (see Burgeff, ; Boullard, ; Iqbal et al, ; Dhillon, ; Nadarajah & Nawawi, ; Moteetee et al, ; Mandyam & Jumpponen, ; Fernández et al, ; Lehnert et al, ; Sudová et al, ; Muthukumar & Prabia, ; Muthuraja et al, ; Lara‐Pérez et al, , for examples) form any kind of mutualistic relationship with pteridophytes has not been explored, but on the evidence to date this would seem unlikely. We are not aware of any published ultrastructural study showing such hyphae in a host cell with healthy cytoplasm in any land plant let alone a pteridophyte, and definitive evidence for a function in seed plants has not yet been forthcoming (Jumpponen & Trappe, ; Jumpponen, ; Newsham, ).…”
mentioning
confidence: 99%
“…Algunas familias como Dryopteridaceae, Equisetaceae, Hymenophyllaceae, Lycopodiaceae y Polypodiaceae (grammítidos) forman asociaciones con HSO que se distinguen por ser dematiáceos a hialinos, con hifas septadas, presencia ocasional de microesclerocios y células moniliformes (Fernández, Messuti, & Fontenla, 2008;Lehnert et al, 2009;Kessler et al, 2009). La presencia de los HSO en las diferentes familias de helechos y licófitas podría sugerir que estos hongos tienen un papel ecológico importante para el crecimiento y desarrollo de las especies.…”
unclassified
“…, Group 2), whereas terrestrial species tend to be consistently mycorrhizal (Fig. , Group 3) with a Paris ‐type colonization pattern .…”
Section: Discussionmentioning
confidence: 99%